Crustaceans of Lendang Luar Beach, Northern Lombok - Ningrum, Audya Septria; Sasmitha, Yuan; Zain, Baiq Kharisma Afrilia Putri; Rosiyani, Amita Dwi; Candri, Dining Aidil; Zamroni, Yuliadi (Samota Journal of Biological Sciences, 2023)
Lendang Luar Beach is a seagrass meadow area with sandy and rocky substrats which located in northern Lombok. This beach has a lot of biota diversity including crustaceans. This research was conducted from June to July 2022. The purpose of this study was to determine the diversity of crustaceans in Lendang Luar Beach. Crustaceans have been observed using purposive sampling method with hand sampling collection. Based on the research results, there were seven families including 11 species, they are Alpheus heterochaelis, Alpheus sp, Calappa japonica, Calappa ocellata, Libinia emarginata, Panulirus versicolor, Percnon gibbesi, Charybdis annulate, Xanto pilipes, Atergatis floridus, and Zosimus aenus. The most dominant species is Alpheus sp. where was collected in rocky areas